(untitled) (Вісник: Міжнародні відносини, 2025)
Background. The protests in Belarus in 2020 had a strong impact on the domestic political situation and significantly affected regional geopolitical dynamics and the transformation of the US and Russian approaches to cooperation with Belarus. While Belarus used to be able to manoeuvre between the West and Russia, the events of 2020 have destroyed the existing balance. Mass demonstrations, the suppression of the protest movement by the Lukashenka regime, and Belarus’ further international isolation led external actors to reconsider their strategies. The United States began to put pressure on the regime through sanctions and provided support to Belarusian civil society in the hope of influencing Lukashenka’s policies. At the same time, Russia used the opportunity to work on deepening integration and increasing Belarus’ dependence on Russia. Methods. The following methods were used in the study: analytical, historical, comparative, prognostic, systematic approach, content analysis. Results. The 2020 protests in Belarus were a natural consequence of growing dissatisfaction with the government’s policies and fatigue with Lukashenka’s long rule. The protests have become a form of public dissent and an attempt to achieve qualitative changes. This crisis also became a catalyst for transforming the approaches of external actors to influence Belarus. Russia took the opportunity to consolidate its control over Belarus, which led to greater cooperation in the military and political sphere and economic integration, which in turn further increased Belarus’ dependence on Russia. In turn, the United States imposed sanctions and politically supported the Belarusian opposition, but failed to have a real impact on Belarus. An analysis of US policy shows the lack of a comprehensive strategy on the Belarusian issue, which makes it difficult to achieve long-term results. However, with Donald Trump coming to power, the US has an opportunity to restart relations with Minsk based on a pragmatic approach. Conclusions. 2020 was a crucial year for Belarus, significantly affecting the domestic political landscape. Despite large-scale protests and strong public discontent, Lukashenka managed to stay in power, but these events led to changes in the geopolitical balance, isolation of Belarus from Western countries, and increasing its dependence on Russia. Russia has protected its strategic interests and strengthened its influence on Belarus, forcing the Lukashenka regime to deepen economic integration and military cooperation, making Belarus extremely dependent on the will of the Russian Federation. For the United States, the events of 2020 were a test of the effectiveness of its policy. Although the US tried to influence Belarus through sanctions and support for the opposition, the effectiveness of such steps was limited. Now the US is trying to find new methods of influencing Belarus, including using sanctions as a subject of bargaining.